Depression among Palestinian Patients on Hemodialysis: Correlates and Outcomes - Ansam Sous; Fatimah Jorf; Mahmoud Taqatqa; Mahdi Allan; Lamees Sawalha; Enas Lubadeh (My University, 2015)
Background:Increasing incidence rates of End Stage Renal Disease (ESRD) among Palestinian patients and its impact on the psychological status of the patient necessitates the importance of increasing knowledge about depression. Purpose:The purposes of this study were to estimate to estimate the prevalence of depression among Palestinian hemodialyzed patients, and its correlation with patients’ clinical characteristics, health related quality of life (HRQoL), and adherence to medications. Methods:A cross-sectional descriptive study using a convenient sample was collected over 3 months from ten hemodialysis centers in West-Bank, Palestine in 2015. The Beck Depression Inventory-II scale (BDI-II) was used to assess depression on participants. The EuroQol-5 Dimension scale was used to assess patients' HRQoL. The Morisky Medication Adherance-8 scale (MMAS-8) was used to confirm compliance. Non-parametric tests (Kruskal Wallis and Mann Whitney tests) of association where appropriately performed to investigate significant effects with depression score. Descriptive statistics were used to describe socio-demographic and disease related clinical characteristics of the patients. All analysis were performed using SPSS version 16.0. Results:A total of 286 hemodialyzed patients were interviewed. The mean age (± standard deviation) of all respondents was (52.0 ± 14.3) years. The majority of participants were male 172 (60.1%), primary educated 132 (46.2%), had low family monthly income 167 (58.4%), married 200 (69.9%), living in the village 185 (64.7%), previously employed 133(46.5%), non-smoker 160 (55.9%), with as many as (74.4%) of them without family history of renal failure. In regard of dialysis characteristics, the median of years of dialysis was 2 years (1-4). The prevalence of depression was 73.1%. Most participants were non-complied to their drug regimens, and had bad HRQoL. Elderly patient ((P = 0.001), female (P = 0.036), low income (P = 0.041) living in rural areas or camp (P = 0.032), not doing regular exercise (P = 0.001), unemployment (P = 0.001), having multi co-morbidities (P = 0.001), low adherence to medications (P = 0.007) are significantly associated with more depression scores. Furthermore, inverse correlation was found between depression and HRQoL; patients with higher depression scores were having lower HRQoL (P = 0.001). Conclusion: This study is the first one confirmed about depression and its prevalence among HD patients in West Bank, in Palestine. The incidence of depression is higher than reported in other communities and has never been approached before. The majority of HD patients were moderately to severely depressed and having bad HRQol